National technology project for the libraries of the Bolivian Catholic University San Pablo (2020–2023) - Lujan, Alfonso Miguel Alarcón; Rosales, Julio Alberto Galarza; Blanco, Andrea Ballivián (Advanced Notes in Information Science, 2024)
Problem: It has not been possible to implement an integrated library management system (SIGB) to unify the use of international standards and appropriate tools to provide services to end users and avoid unnecessary duplication of efforts in the different libraries at headquarters. Objective: This study aims to enhance the national library system (SINAB) by incorporating regulations and organizational structure of the SINAB and national acquisition and subscription of virtual resources, implementing an integrated Universidad Católica Boliviana San Pablo (UCB) library system (KOHA), and developing a national UCB libraries system web page as a tool that gathers all the university services for the support of learning, teaching, and research that benefit the UCB academic community. Methodology: For the development, drafting, and approval of the project, the project management body of knowledge (PMBOK) tool was used. According to PMBOK definitions, a project is a temporary effort undertaken to create a unique product, service, or result. In simple terms, a project can be any action that needs to be taken to accomplish something new. This can go beyond the business context, as it can encompass launching a product, starting a new course, and even making major purchases. Results and discussion: The study achieved several key outcomes, including subscription to 12 virtual tools and resources, all included in the NEO; learning; implementation of the SIGB KOHA in the four UCB sites, which are now in operation; creating tutorial videos; regulations of SINAB-UCB, approved by the Board of Directors; and a call for the creation of the national web page.